The ulama of Palembang Sammaniyah order: Survival in the middle of the regime of power in the 20th century - Kurniawan, Rudy (HTS teologiese studies, 2022)
During the Palembang Sultanate, the Sammaniyah order was the official religion of the Palembang palace. Sammaniyah tariqa scholars were also made officials and advisers to the sultan. This article aims to discuss the power relations of the Palembang Sammaniyah ulama in terms of continuity and change in the regime of power. From the 19th to the 20th centuries, the Sammaniyah tariqa lived and developed under five regimes of power, namely the Sultanate of Palembang Darussalam, the Dutch colonists, the Japanese invaders, the Old Order and New Order. Palembang Sammaniyah tarekat scholars who are considered conservative (kaum tuo) have to deal with modern scholars (kaum mudo) because of the khilafiyah problem. As a result, there was a great shift by the Sammaniyah ulama in maintaining and developing the Sammaniyah order in Palembang. Firstly, the shift occurred in the role and function of the ulama of the tarekat, changing from religious leaders who teach Islamic religious knowledge to multifunctional scholars in dealing with modernism by utilising public space. Secondly, the charismatic nature of the Sammaniyah tarekat ulama formed the authority of the ulama so that the ulama could play a role in sociopolitical affairs in each power regime. Thirdly, contemporary tarekat scholars and Sammaniyah tarekat scholars who are considered conservative scholars could compete with mudo people who were considered religious reformers. Besides, the ongoing Islamisation challenged the Sammaniyah tariqa scholars in maintaining and developing the Sammaniyah tariqa.Contribution: This research will contribute to determining the relationship between power and the existence of scholars. The question that the article tries to explore is how the identity and existence of the ulama could survive every change of power in Palembang. This article will discuss the changes in power that have occurred in each period that caused a change in mindset and a shift in the identity of the ulama. This study discusses the power relations of the Palembang Sammaniyah ulama in changing regimes of power and finds the fact that power can affect the order.